PEMBERIAN KEGIATAN MINDFULNESS PADA ANAK PANTI ASUHAN - Widiasavitri, P.N.; Lestari, M.D.; Suarya, L.M.K.S.; Rustika, I.M. (Buletin Udayana Mengabdi; Vol 16 No 2 (2017), 2017)
Mindfulness is a state of awareness which occurs when we attend the present time and focus to our goals, without giving judgement to each and every experiences. Mindfulness for children can increase their level of concentration and lower their anxiety and stress level. These mindfulness activities were held on our community service program, and aimed to increase the level of concentration. These mindfulness activities were held for four weeks. Savoring "beng-beng" was the activity in our first week. The second week's activity was done by coloring with mindfulness. In the third week, we did the body scanning, and the fourth week was done by "breathing". The briefing for these activities was done by October 9, 2016. All of the orphanage's members were briefed, but only five members were involved in this mindfulness treatment. The number subtests in Weschler Intelligence Scale for Children (WISC) were used as the pre-test and post-test. As the result, there were increase on the score of number subtests in WISC. This result indicates that are improvements in children's concentration level.